A Qualitative Content Analysis of Online Public Mental Health Resources for COVID-19 - Martin, Faith; Oliver, Thomas (Frontiers in Psychiatry, 2022)
The COVID-19 pandemic has far reaching potential public mental health impacts and is linked to higher levels of depression and anxiety. To address these in part, online information resources acted as mass interventions. It is vital to explore the content of these interventions, to consider the framing of the pandemic and to examine the extent to which their content is relevant. In March 2020, a qualitative content analysis was undertaken of 39 easily accessible online resources that offered advice, tips or guidance relating to mental health or mental wellbeing and COVID-19. Their content was compared to subsequent reports of the mental health impact of the pandemic. Resources frequently focused on anxiety. The content of intervention was typically of a cognitive-behavioural nature, with a significant focus on maintaining social contact. Typically, distress related to the situation was normalized and stigmatizing language was not seen. Data revealed a significant impact of the pandemic on depression as well as anxiety measures in the general UK population. A key recommendation is to ensure both depression and anxiety are addressed in these public mental health resources.